Analisis Relevansi Pendidikan Agama Kristen Di Universitas - Junio Richson Sirait; Hestyn Natal Istinatun (Jurnal Indragiri Penelitian Multidisiplin, 2022)
Religious Education, including Christian Religious Education for every Christian student, is a subject that must be taught at educational institutions specifically in Indonesia. However, many students today are more oriented to the development of scientific competence in their field of study and ignore general compulsory subjects such as Christian Religious Education. The goals and targets to be achieved are to find out the relevance of Christian Religious Education at the University with the hope of discovering the role and impact of learning on student life as a whole and correctly. The problems contained in Christian Religious Education were studied using a qualitative descriptive method with a content analysis strategy. Through this study, it was concluded that Christian Religious Education is still relevant to be taught in all universities because it has an important role in spiritual, moral, and social development.